Exploring the Evolution of Waqf Laws and Contemporary Practices in Muslim Countries - Iskandar Iskandar; Hadi Sofuoğlu (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
Muslim countries. Throughout Islamic history's trajectory, waqf has served as a crucial element in the advancement of Islamic civilization. It has substantially contributed to religious, social, educational, economic, and community progress. To ensure the effective preservation and management of waqf assets, the presence of a robust waqf law that serves as a guiding framework is indispensable. In modern times, the legislation pertaining to waqf in Muslim countries has undergone significant evolution and enhancement. However, waqf laws in Muslim countries are subject to change. This paper employed a qualitative research method using secondary data to analyze the evolution and contemporary practices of waqf laws in Muslim countries. The result of this study found that waqf laws in Muslim countries have experienced multiple reforms, with the number of changes varying across different nations. Reforms in waqf laws across Muslim countries demonstrate ongoing efforts to enhance the legal frameworks governing waqf management and administration, addressing the evolving needs and challenges associated with waqf properties. These reforms aim to ensure efficient utilization and management of waqf assets for the betterment of society.